Combined GPS and BeiDou Instantaneous RTK Positioning. Issue 2 (June 2014) - Odolinski, Robert; Odijk, Dennis; Teunissen, Peter J.G.
ABSTRACT The Chinese BeiDou‐2/COMPASS Navigation Satellite System has attained regional operational status and is expected to reach the same level of popularity as GPS once it has reached its full constellation. This contribution considers combined BeiDou+GPS relative code positioning and single‐ and multiple‐frequency real‐time kinematic (RTK) positioning. A combined system increases the redundancy for solving the unknown GNSS parameters and thus allows for more precise position estimates, improved reliability and robustness against failure of any of the systems. The performance is evaluated by ambiguity success rates and by comparing the estimated positions to very precise benchmark coordinates. We make use of the LAMBDA method for integer ambiguity resolution, in combination with the Fixed Failure‐rate Ratio Test to validate the resolved ambiguities. The combined model will be shown to allow for improved ambiguity resolution performance and positioning robustness and accuracy over the BeiDou‐ and GPS‐only solutions. Copyright © 2014 Institute of Navigation.